North Carolina in the Connected Age : Challenges and Opportunities in a Globalizing Economy - Walden, Michael L. (Michael Leonard), 1951- (Book collections on Project MUSE., 2008)
Despite almost four centuries of black independent self-help enterprises, the agency of African Americans in attempting to forge their own economic liberation through business activities and entrepreneurship has remained noticeably absent from the historical record. Juliet Walker's award-winning History of Black Business in America is the only source that provides a detailed study of the continuity, diversity, and multiplicity of independent self-help economic activities among African Americans. This new, updated edition divides the original work into two volumes. The first volume covers Afric.